Thermal Energy Optimization of Building Integrated Semi-Transparent Photovoltaic Thermal Systems - Ekoe A Akata Aloys Martial; Donatien Njomo; Basant Agrawal (Center of Biomass & Renewable Energy (CBIORE), 2015)
Building integrated photovoltaic (BIPV) : The concept where the photovoltaic element assumes the function of power generation and the role of the covering component element has the potential to become one of the principal sources of renewable energy for domestic purpose. In this paper, a Building integrated semitransparent photovoltaic thermal system (BISPVT) system having fins at the back sheet of the photovoltaic module has been simulated. It has been observed that this system produces higher thermal and electrical efficiencies. The increase of wind velocity by fan system and heat exchange surface accelerates the convective heat transfer between the finned surface and the fluid flowing in the duct. The system area of 36.45 m2 is capable of annually producing an amount of thermal energy of 76.66 kWh at an overall thermal efficiency of 56.07 %.